Radiation-inducible Immunotherapy for Cancer: Senescent Tumor Cells as a Cancer Vaccine - Meng, Yuru (Nature Publishing Group, 2012)
Radiotherapy offers an effective treatment for advanced cancer but local and distant failures remain a significant challenge. Here, we treated melanoma and pancreatic carcinoma in syngeneic mice with ionizing radiation (IR) combined with the poly(ADP-ribose) polymerase inhibitor (PARPi) veliparib to inhibit DNA repair and promote accelerated senescence. Based on prior work implicating cytotoxic T lymphocytes (CTLs) as key mediators of radiation effects, we discovered that senescent tumor cells induced by radiation and veliparib express immunostimulatory cytokines to activate CTLs that mediate an effective antitumor response. When these senescent tumor cells were injected into tumor-bearing mice, an antitumor CTL response was induced which potentiated the effects of radiation, resulting in elimination of established tumors. Applied to human cancers, radiation-inducible immunotherapy may enhance radiotherapy responses to prevent local recurrence and distant metastasis.